The Effect Of Facilities and Comfort On Customer Satisfaction: The Services as an Intervening - Yulina Eliza, et Al. (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
This study aims to identify and analyze the factors that influence Customer Satisfiction KM Ambu-Ambu In Mentawai Islands. Methodology/approach - This study uses a quantitative method, because it meets scientific principles, namely concrete, objective, measurable, rational and systematic. Data collection techniques is conducted by giving or distributing a list of questions to respondents in the hope that they will respond to the list of questions. The research instrument uses validity, reliability, and classic assumption tests. Then to test the Path Analysis hypothesis is by using SPSS.Findings - Facilities and convenience have a significant effect on consumer satisfaction, while services are not significant on consumer satisfaction. to get to the service is influenced by facilities and comfort. furthermore, facilities and comfort are not significant to consumer satisfaction due to intervening in the form of services. Novelty/value - In light of this, we believe it is crucial to examine how comfort and failure affect satisfaction in KM vessels. Ambu-Ambu. An overview of the impact of amenities and comfort on patron satisfaction at KM Ambu-Ambu is given in this article.